Getting started in consulting - Weiss, Alan, 1946-; Safari eBooks (Hoboken, N.J. : John Wiley & Sons, 2009)
"For almost a decade, Alan Weiss's Getting Started in Consulting has been an indispensible resource for anyone who wants to strike out on his own and start a new consulting business. It provides a rich source of expert advice and practical guidance, and it shows you how you can combine low overhead and a high degree of organization to add up to a six- or even seven-figure income. You'll learn everything you need to know about financing your business, marketing your services, writing winning proposals, meeting legal requirements, setting fees, keeping the books, and much more"--Cover, p. 4.
Establishing goals and expectations (including your own) -- Physical space and environmental needs -- Sorting out the legal, financial, and administrative first -- Marketing 101 -- Advanced marketing -- Initiating the sales process and acquiring business -- Closing the sale -- Establishing fees -- Moving to the next level -- Giving yourself permission to succeed -- The quick start.
Description based on print version record.
Includes indexes.
Keywords: Business consultants -- Handbooks, manuals, etc; Consultants -- Marketing -- Handbooks, manuals, etc; Electronic books